Active adenoviral vascular penetration by targeted formation of heterocellular endothelial-epithelial syncytia. - Chen, H; Cawood, R; El-Sherbini, Y; Purdie, L; Bazan-Peregrino, M; Seymour, L; Carlisle, R (2011)
The endothelium imposes a structural barrier to the extravasation of systemically delivered oncolytic adenovirus (Ad). Here, we introduced a transendothelial route of delivery in order to increase tumor accumulation of virus particles (vp) beyond that resulting from convection-dependent extravasation alone. This was achieved by engineering an Ad encoding a syncytium-forming protein, gibbon ape leukemia virus (GALV) fusogenic membrane glycoprotein (FMG). The expression of GALV was regulated by a hybrid viral enhancer-human promoter construct comprising the human cytomegalovirus (CMV) immediate-early enhancer and the minimal human endothelial receptor tyrosine kinase promoter ("eTie1"). Endothelial cell-selectivity of the resulting Ad-eTie1-GALV vector was demonstrated by measuring GALV mRNA transcript levels. Furthermore, Ad-eTie1-GALV selectively induced fusion between infected endothelial cells and uninfected epithelial cells in vitro and in vivo, allowing transendothelial virus penetration. Heterofusion of infected endothelium to human embryonic kidney 293 (HEK 293) cells, in mixed in vitro cultures or in murine xenograft models, permitted fusion-dependent transactivation of the replication-deficient Ad-eTie1-GALV, due to enabled access to viral E1 proteins derived from the HEK 293 cytoplasm. These data provide evidence to support our proposed use of GALV to promote Ad penetration through tumor-associated vasculature, an approach that may substantially improve the efficiency of systemic delivery of oncolytic viruses to disseminated tumors.